KEABSAHAN PERJANJIAN SIMULASI DALAM BENTUK AKTA NOTARIS DITINJAU DARI ASAS ACTA PUBLICA PROBANT SESE IPSA - Safira Wijaya (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this study is find out the validity of the simulation agreement in the form of a notarial deed in terms of the acta publica probant sese ipsa principle and secondly to find out the legal agreement of the relationship agreement of the first and the following agreement. This study uses a normative legal research method with a statutory approach. The result of this study is that a simulated agreement in the form of an authentic deed/notarial deed has legal defects when viewed using the theory of the validity of the agreement. However, it can be said differently when viewed using the principle of acta publica probant sese ipsa. The legal consequences of absolute (absolute) simulation agreements and relative simulation agreements can be different. The legal consequences can be in the form of a change or transfer of rights to the object of the agreement and no change or transfer of the object of the agreement.